HEMATOPOIETIC STEM CELL TRANSPLANTATION FOR MYELODYSPLASTIC SYNDROMES - Duarte, Fernando Barroso; Karine Sampaio Nunes Barroso; Roberto Luiz da Silva; Lívia Andrade Gurgel; João Paulo de Vasconcelos Leitão; Beatriz Stela Gomes de Souza Pitombeira; Rodolfo Daniel de Almeida Soares; Leandro de Pádua; Gustavo Betarello (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
The document discuss key points in the management of patients with Myelodysplastic Disease, including therapeutic strategies, the role of new drugs available as well the Hematopoietic Stem Cell Transplantation. Other issues evaluated were importance of molecular alterations since diagnosis to prognosis, use of comprehensive geriatric assessment for patient's selection, individualization of treatment, donor selection for HSCT and the role of blasts % and molecular mutations for the appropriate diagnosis.